Situation Based Solid Wastes Source Characterization: The Kibuye Market and Other Peri-urban Ward Units -Kisumu City (Kenya) - Aguko, Kabok P.; Awuor, Frankline Otiende; Oloko, Michael O. (International Journal of Emerging Technology and Advanced Engineering, 2020)
Solid Wastes managemeorigionant (SWs) characterization and 3Rs benefit is lacking and an integral problem of Kisumu city today, at best a scavenging level effort that needs a shift. The study characterized and quantified SWs streams because of the varied reported estimates. Also, it was for finding a cheap and sustainable participatory approach of characterizing the daily generation. The study area choice was then based on existence of waste pickers for a fee and the organic matter at Kibuye market. Data was collected by pre-trained waste actors and market representatives. Generation rates (2010 to 2015) by researchers averaged 200 to 450 tons daily, against 135 to 400 tons daily from present and a previous study, at a base population of 500,000. 400 tons daily also has been quoted and used, as Kisumu city strategy paper up to 2025 suggests 210 tons daily. These points to need for a comprehensive re-check of the values. Organizing waste management today require understanding of its dispersed nature, material characteristics, unit associations, enforcement of weighing, the law and Service Centers for data collection for planning, as there is little to show from Kisumu today.
Keywords: Solid Waste; Characterization; Waste Pickers; Participatory Approach; Service Centers.